Diabetes Mellitus, Edentulism, and Trajectory of Cognitive Decline Among Older Adults. (17th December 2021) - Wu, Bei; Tan, Chenxin; Plassman, Brenda; Sloan, Frank; Schwartz, Mark; Adhikari, Samrachana; Kamer, Angela; Luo, Huabin
Abstract: We examined the impact of diabetes mellitus (DM) and edentulism on the trajectory of cognitive decline, using the Health and Retirement Study. We analyzed self-reported DM and edentulism collected in 2006 and cognition data from 2006 and its follow up waves through 2018. Among 15, 709 eligible participants age 50+ in 2006, 65.96% had neither DM nor edentulism (Group 1), 15.12% had DM alone (Group 2), 13.79% had edentulism alone (Group 3), and 5.12% had both conditions (Group 4). Results from linear mixed-effects models show that in comparison to Group 1, individuals in Group 4 had the lowest level of cognitive function, followed by those in Group 3 and Group 2. Group 4 had a modestly faster rate of cognitive decline (p=0.052). This study illustrates that co-occurrence of DM and edentulism has a higher risk of more rapid cognitive decline with advancing age than the presence of each condition alone.